Exploration and Practice of the Acquisition Path of Spoken English for Special Purposes with the Blockchain Technology - Ruan, Yali (Mobile information systems, 2022)
With the increasing trend of globalization, English, as the most widely used language in the world, has become a subject that many people must learn. English for special purposes is mainly applied to some specialized occupations or English in specific professional skill fields. Due to the increasing national demand for professional compound talents, the status of English for special purposes is also getting higher and higher. However, there are still many problems in the curriculum setting of English for special purposes, for example, outdated teaching mode, lack of oral language skills training, lack of students’ ability to cope with actual situations, weak teaching awareness of teachers, and lack of analysis of students’ needs for English for special purposes, resulting in poor students’ enthusiasm for learning and so on. With the support of blockchain technology, combined with consensus algorithm, hash function algorithm, and smart contract, this paper analyzes English for special purposes, establishes an ESP management system and a corpus of spoken English for special purposes, and analyzes the integrity of the corpus data. The test found that when the number of error data blocks is 10, the total number of damaged data blocks and verification accuracy data blocks is about 4% in order to achieve 99% accuracy. Therefore, the integrity of the system is higher when the damage ratio is lower. The system integrity test finds that, with the number of wrong data being larger, when the wrong data block is at 100, 50% of the data blocks of the system integrity are about 1%. The database is complete, which is more helpful for students to study systematically.